Burnout y afrontamiento en un grupo de agentes de tráfico del aeropuerto - Quiros Seminario, Silvana María (2013)
This research seeks to determine the levels of burnout as well as the relationship amongst its components (emotional exhaustion, depersonalization and personal accomplishment) and the coping styles and strategies in a group of 60 air traffic controllers, aged between 26 and 59, who work for several airlines at an airport in this country. For this purpose, the tests used were the Maslach Burnout Inventory (MBI) and the Coping Inventory, COPE. It was found that 35 % of the sample had developed Burnout Syndrome. It was also found that the group prone to burnout and the risk group represented 25% and 26%, respectively. This is alarming due to the physical and psychological consequences that the syndrome entails. Furthermore, it was found that problem-focused style correlated positively with personal fulfillment, and that avoidant styles related to all dimensions of burnout. Moreover, personal fulfillment is the dimension that has more associations.